Male Social Constructions in the Novel Interior Chinatown by Charles Yu - Neisya, Neisya; Aprilia, Fitria; Dewiyanti, Elisa (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Gender is a social construction through which individuals relate to their social environment. The social construction of gender dictates the masculine and feminine roles deemed appropriate within a society. The study aims to explore how Wu's character in the novel Interior Chinatown and his interactions sheds light on the challenges faced by Asian Americans in navigating their cultural heritage within a predominantly white society. The research method used in this study is qualitative research. Specifically, the study uses descriptive research primarily focusing on describing the characteristics of the main character. The research method involves collecting and analyzing data showing the forms of social constructions and the impact on Wu’s personality based on Burr’s masculinity theory. In the technique for collecting data, the researchers read the novel, then underline and write the dialogue contained the social construction in the novel, and the last collect the data of sentence that have been underlined. For the technique for analyzing data, the researchers classify and categorize the data scenes also dialogue that show the social construction and its impact of Willis Wu’s personality based on Burr’s perspective. The results of this study include the forms of social constructions contained in the novel Interior Chinatown consist of two types, namely social construction caused by race and media. Meanwhile, the impacts of social constructions on Willis Wu’s personality are included two types; frustration and ambition. The researchers conclude that social construction plays a significant role in shaping individuals' lives and opportunities.